Morphological Characteristics and Kinship Relationships of Salak Pace, Salak Hitam, and Salak Kuning in Bedahlawak Jombang - Mohammad Suud Wahyudi; Mazidatul Faizah; Siti Aminatuz Zuhria (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Indonesia has a lot of fruits. One of them is salak fruit. This study was prepared to determine the morphological characteristics and kinship relationships of salak pace, black salak, and yellow salak plants. This research was conducted in Bedahlawak Village, Tembelang District, Jombang Regency. This research was conducted in February-April 2021 by selecting 5 samples from each type of salak plant with research parameters of plant height, leaf length, leaf width, leaf tip shape, leaf tension distance, top surface color of leaves, color of the underside surface of the leaves. The research was conducted by conducting direct observations and compiled using descriptive methods and analyzed using cluster analysis in the form of similarity dendograms. Based on vegetative morphological observations, characteristics on the parameters of plant height, leaf length, upper surface color of leaves, color of the underside of the leaves, length of the pelepah, length of thorns, shape of thorns, texture of thorns, distance of thorn density, length of roots and have a distant kinship relationship by showing a similarity value of 56%-63%.